A novel index to classify vertical jump performance of athletes according to the body mass - Kulkamp W.* (2021)
© 2021. Faculty of Education. University of Alicante. All Rights Reserved.Purpose: this study aimed to present a novel index to classify athletes using jump height (JH) as an indicator of lower limb performance considering different levels of body mass (BM). Methods: Three hundred fourteen male athletes volunteered to participate of this study. The athletes were evaluated performing the countermovement jump. Sigmoid functions were used to estimate the JH median according to the athlete's BM and peak power output (PPO). The Jump Sigma Index was proposed, dividing the measured JH by predicted JH for BM or PPO. This index is a percentage metric that allows one to classify the athletes' JH in four levels (Superior, Median-Superior, Median-Inferior, Inferior). Sigmoid functions (r2 =. 99; p <. 01) were used as an explanatory model for the relationship of JH medians with BM (SigmaBM) and PPO (SigmaPPO) medians for each BM interval. Results: The applicability of the method was verified by the high correlations observed between SigmaBM and SigmaPPO (r =. 985, p <. 01). The total error of the classification model in the four levels was only 7.9% when comparing the classifications from SigmaBM and SigmaPPO (Kappa =. 88; p <. 01), indicating almost perfect agreement. Conclusion: The Jump Sigma Index (SigmaBM) is a valid and practical index for classifying athletes using only JH and BM as indicators of lower limb performance.